ZnS/Cu2ZnSnS4/CdTe/In Thin Film Structure for Solar Cells - Jafarov, Maarif Ali; Nasirov, E.F.; Jahangirova, S.A. (JOURNAL OF ADVANCES IN PHYSICS, 2018)
A solar cell with glass/ITO/ZnS/Cu2ZnSnS4/CdTe/In structure has been fabricated using all-electrodeposited ZnS, Cu2ZnSnS4 and CdTe thin films. The three semiconductor layers were electrodeposited using a two-electrode system for process simplification. The incorporation of a wide bandgap amorphous ZnS as a buffer/window layer to form ITO/ZnS/Cu2ZnSnS4/CdTe/In solar cell resulted in the formation of this 3-layer device structure. This has yielded corresponding improvement in all the solar cell parameters resulting in a conversion efficiency >12% under AM1.5 illumination conditions at room temperature. These results demonstrate the advantages of the multi-layer device architecture over the conventional 2-layer structure.